Efficacy of granisetron in the prevention of nausea and vomiting among paediatric oncology patients receiving moderate to highly emetogenic chemotherapy : a single-blinded, non-inferiority trial - Chong, Doris Sie Lau; Soh, Cheng Khai; Loh, C-Khai; Syed Zulkifli Syed Zakaria,; Hamidah Alias, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This single-blinded, non-inferiority trial was conducted over an 8-month period to examine the efficacy of intravenous granisetron at two differing doses in preventing acute and delayed chemotherapy-induced nausea and vomiting (CINV) among paediatric patients receiving moderate to highly emetogenic chemotherapy. Seventeen patients (9 males and 8 females) were recruited and randomly assigned to receive alternating granisetron dosages of 0.01 mg/kg and 0.04 mg/kg during each chemotherapy cycle. The severity of CINV during and three days post-completion of chemotherapy, as well as common side effects of granisetron were recorded. A total of 78 cycles of chemotherapy (38 cycles of 0.01 mg/kg and 40 cycles of 0.04 mg/kg) were evaluated. The median age of the study population was 5.2 years (interquartile range 25th, 3.8; 75th, 8.7). Patients’ diagnoses comprised of haematological malignancy, bone tumour and cerebral neoplasm. From this study, we demonstrated that intravenous (IV) granisetron 0.01 mg/kg was non-inferior to 0.04 mg/kg in terms of achieving a complete response for acute CINV. However, a similar observation was not seen in the post-treatment period analysis (delayed CINV). In conclusion, IV granisetron at 0.04 mg/kg/dose provides effective protection and prophylaxis of both acute and delayed CINV. Further study with a larger sample size may be required before a definite conclusion can be made with regards to efficacy of 0.01 mg/kg dose.